Impact of dielectric substrate on the performance of an 8 × 8 magneto-electric dipole phased array antenna for 5G mmWave applications - Yong, Wai Yan; Alayón Glazunov, Andrés (Frontiers in Communications and Networks, 2023)
The impact of the substrate dielectric material on the performance of a wideband magneto-electric dipole (MED) phased array antenna is systematically studied in this article. Four commercially available dielectric substrates for mmWave applications, i.e., Rogers RO 5880, RO 3003, RO 4350B, and Panasonic Megtron-6, are considered in the design investigation of the proposed MED phased array antenna. First, the influence of the dielectric constant on the operating frequency of the unit cell MED antenna is explored in the broadside direction ($θ = 0^{°}$). Second, the scanning impedance is assessed at various scanning angles for both E- and H-plane scanning. Finally, the radiation performance of the proposed design of a finite $8×8$ MED phased array antenna is examined. This study gives a foundational understanding of the impact of dielectric characteristics on the performance of MED phased arrays.The analysis revealed that the MED phased array antenna based on substrates with a higher dielectric constant exhibited a smaller scanning angle than the substrate with a lower dielectric constant. The findings may serve as practical guidelines for selecting the dielectric substrates for the 5G mmWave phased array antenna in order to adapt their design to an application's specifications.